Driving Entrepreneurial Performance in MSMEs: The Role of Management Control Systems, Innovation Capability and Digital Technology - Rizaldi Yusfiarto; Hisham Al Ghunaimi; Dzikria Al Haq; Isma Hisbullah Al Jauhany (EkBis: Jurnal Ekonomi dan Bisnis, 2026)
This study examines the drivers of entrepreneurial performance in Indonesian Micro, Small, and Medium Enterprises (MSMEs) by integrating the Resource-Based View and Dynamic Capabilities Theory. Using a cross-sectional survey of 296 MSME owners and managers across Indonesia and analyzing the data with Partial Least Squares Structural Equation Modeling. The findings show that all four factors significantly and positively contribute to improving MSME performance, highlighting the complementary roles of strong internal organizational systems and external strategic networks. These results suggest that MSMEs that combine effective managerial controls, innovation-oriented processes, digital technology adoption, and collaborative business relationships are better positioned to achieve superior entrepreneurial outcomes in dynamic market environments. By proposing and empirically validating an integrated RBV–DCT framework in the MSME context, this research provides a holistic perspective that extends prior fragmented approaches and enriches the understanding of entrepreneurial performance in emerging economies such as Indonesia.